Guide for the format, content and submission of preliminary information under Chapter 4 of the Environment Protection and Biodiversity Conservation Act 1999. - Australia. Environment Australia (Canberra : Enivronment Australia, 2000)
This guide has been prepared by Environment Australia to assist people to prepare and submit preliminary information for the environmental assessment and approval process under Chapter 4 of the Environment Protection and Biodiversity Conservation Act 1999 (EPBC Act)
Format of preliminary information -- Content of preliminary information -- Information sources -- Part 1. General requirements -- pt. 2. Information requirements for assessment under section 162 of Act.
Caption title.
"September 2000" -- p. 4.
Keywords: Australia; Environmental protection -- Australia; Conservation of natural resources -- Australia -- Citizen participation; Biodiversity conservation -- Australia -- Citizen participation; Environmental law -- Australia